PENERAPAN MODEL KOOPERATIF TIPE GROUP INVESTIGATION (GI) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA PADA SISWA KELAS V SD N 2 LAMUK KEJOBONG-PURBALINGGA TAHUN 2013/2014 - Setyadi, Epri (KALAM CENDEKIA PGSD KEBUMEN, 2015)
Abstract: Application of Cooperative Model Type Group Investigation (GI) To Improve Mathematic Learning Outcomes In Students Class V SD. This research aims to: describe the steps model (GI), improving the learning outcomes of Mathematics, describe the constraints and solutions in the application of (GI). This study was conducted in three cycles the subject of fifth grade students SD N 2 Lamuk totaled 19 people. Data were analyzed using qualitative data and quantitative. The results showed: Step (GI) is, grouping, planning, investigation, organization, presentation, and evaluation. The results of learning Mathematics increased from 3 cycles indicated by the thoroughness of 47,36 %, 81,57 % and 89,47 %. The conclusions of this study are the application of model Group Investigation (GI) can improve Mathematic Learning Outcomes In Students Class V SD N 2 Lamuk. Keywords: Group Investigation (GI), Learning Outcomes, Mathematics Abstrak: Penerapan Model Kooperatif Tipe Group Investigation (GI) Untuk Meningkatkan Hasil Belajar Matematika Pada Siswa Kelas V SD. Penelitian ini bertujuan untuk: mendeskripsikan langkah-langkah (GI), meningkatkan hasil belajar Matematika, mendeskripsikan kendala dan solusi penerapan (GI). Penelitian ini dilaksanakan dalam tiga siklus dengan subjek siswa kelas V SD N 2 Lamuk berjumlah 19 orang. Teknik analisis data menggunakan data kuantitatif dan kualitatif. Hasilnya: Langkah (GI) yaitu pengelompokkan, perencanaan, penyelidikan, pengorganisasian, presentasi, dan evaluasi. Hasil belajar Matematika dari 3 siklus meningkat ditunjukkan dengan ketuntasan 47,36%, 81,57% dan 89,47%. Kesimpulannya penelitian ini adalah penerapan model Group Investigation (GI) dapat meningkatkan hasil belajar Matematika siswa kelas V SD N 2 Lamuk. Kata kunci: Group Investigation (GI), Hasil Belajar, Matematika